Barbara [videorecording (DVD)] - Petzold, Christian, 1960-; Hoss, Nina; Zehrfeld, Ronald, 1977-; Bock, Rainer (Schramm Film Koerner & Weber, 2013)
East Germany, 1980. Barbara Wolff is a young doctor who has applied for an exit visa from the GDR and, as punishment, has been transferred from her prestigious post in Berlin to a small pediatric hospital in the country. She must weigh her absolute dedication to her patients against a potential escape to the West, and her newfound attraction to a doctor in whom she sees a kindred spirit.